Japanese economy - Ito, Takatoshi (London Cambridge, 2020)
The second edition of a comprehensive account of all the major aspects of the Japanese economy, substantially updated and expanded.
Revised edition of The Japanese economy, c1992.
Keywords: Japan--Economic conditions--1945-